The role of organizational justice in promotion decisions - Lazauskaitė-Zabielskė, Jurgita; Bagdžiūnienė, Dalia (Psichologija, 2008)
Organizational justice perceptions are important for organizations, because they help to predict organizationally important outcomes. However, justice regarding promotions in particular is studied less than other types of organizational justice. Therefore the research was conducted to examine the role of organizational justice aspects, i. e. distributive, procedural and interactional justice, in promotion decisions. The purpose of this study was to determine how perceived distributive, procedural and interactional justice are related to favourability of promotion decision and various levels of outcomes. In particular, this study explored the relationship between perceived distributive, procedural and interactional justice and job satisfaction, satisfaction with promotion opportunities, organizational commitment, turnover intentions, trust in supervisor and trust in management. 132 employees from various organizations participated in the study. The results of the study revealed that favourability of promotion decision (i. e. promotion or non-promotion) is related to perceived distributive justice (Z = –5.867, p ≤ 0.001), but not related to perceived procedural and interactional justice. While perceived justice of decision is related to decision favourability, fair procedures and fair interpersonal treatment is valued irrespective of it. The study also showed that different aspects of organizational justice are related to different outcomes. Perceived distributive justice is related to job satisfaction (β = 0.602, p ≤ 0.01) and satisfaction with promotion opportunities (β = 0.721, p ≤ 0.01). The more decision regarding promotion is considered as fair the more employees are satisfied with their job and promotion opportunities. Perceived procedural justice is the best predictor of organizational outcomes such as organizational commitment (β = 0.676, p ≤ 0.01) and turnover intentions (β = 0.687, p ≤ 0.01). When employees perceive promotion procedures as fair they are more committed to organization and less likely to leave. Moreover, perceived interactional justice is positively related to satisfaction with promotion opportunities (β = 0.138, p ≤ 0.01). Finally, when promotion decisions are made by supervisor, perceived interactional justice is positively related to trust in supervisor (β = 0.716, p ≤ 0.01). On the other hand when promotion decisions are made by upper-level manager, perceived interactional justice is positively related to trust in management (β = 0.682, p ≤ 0.01). Limitations of the study and possibilities for future researches and practical applications are discussed.